Market integration and the long run adjustment of local markets to changes in trade and exchange rate regimes: options for market reform and promotion policies - Badiane, Ousmane (International Food Policy Research Institute, 1997)
Market integration analysis may be helpful in providing a photograph of the operation of local markets at a given point in time. However, the process of market reform in the context of structural and institutional deficiencies, rather than being a one-shot issue, involves a lengthy transition process from a state-run to a private-sector-based distribution system. Unless it is extended to examine, among others, how market integration affects the process of adjustment in local markets, integration analysis will be of limited help as a tool for market policy research. The approach outlined in the present paper proposes an extension that is based on two premises. First, that the impact of the shock in the central market prices does not only affect the short term level of the local prices, but also their time path. That second, long term impact is determined by the degree of integration and is affected by any accompanying changes in local arbitrage costs.